2021
DOI: 10.1073/pnas.2018640118
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in gene expression noise by targeted increase in accessibility at gene loci

Abstract: Many eukaryotic genes are expressed in randomly initiated bursts that are punctuated by periods of quiescence. Here, we show that the intermittent access of the promoters to transcription factors through relatively impervious chromatin contributes to this “noisy” transcription. We tethered a nuclease-deficient Cas9 fused to a histone acetyl transferase at the promoters of two endogenous genes in HeLa cells. An assay for transposase-accessible chromatin using sequencing showed that the activity of the histone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
2
21
1
Order By: Relevance
“…We showed that by increasing histone acetylation via treatment with the HDAC inhibitor trichostatin A (TSA), we could lower gene activation noise. This result is consistent with a more recent and experimentally elegant study demonstrating that increasing histone acetylation via targeted recruitment of the histone acetyltransferase p300 similarly decreased noise in gene expression following TF stimulation [71]. Our model experimentally reproduces this result (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that by increasing histone acetylation via treatment with the HDAC inhibitor trichostatin A (TSA), we could lower gene activation noise. This result is consistent with a more recent and experimentally elegant study demonstrating that increasing histone acetylation via targeted recruitment of the histone acetyltransferase p300 similarly decreased noise in gene expression following TF stimulation [71]. Our model experimentally reproduces this result (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…e Distance in base pairs from the isoform start to the nearest CAGE peak summit from Ref. [43]. f HOTAIR exon E7 diagram showing 3’ end polyA tails.…”
Section: Resultsmentioning
confidence: 99%
“…Full-length gels are presented in Additional file 3 Fig.S6. c IGV tracks over HOTAIR locus showing predicted HOTAIR regulatory elements (REMs) from the EpiRegio database [44, 60] (red: activating, blue: repressing), average ATAC-Seq tracks from ASCs [40, 41], Myoblasts [42] and HeLa cells [43], and ChIP primers location. d ChIP-qPCR analysis of histone modifications during adipogenesis of ASCs (mean ± SEM of n ≥ 3 independent differentiation experiments; **p < 0.01 Mixed effect analysis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in single-cell technologies have exposed remarkable differences in phenotype and expression patterns between individual cells within the same isogenic cell population [1]- [9]. While some of this variation can be linked to extrinsic factors (i.e., cell-cycle stage, cell size, local extracellular environment), increasing evidence points to the role of stochastic processes inherent to gene expression in driving random fluctuations (noise) in gene product levels [10]- [24]. This intercellular phenotypic heterogeneity can play important functional roles in diverse biological processes, from driving genetically-identical cells to different cell fates [25]- [35] to allowing microbes and cancer cells to hedge their bets against uncertain environmental changes [36]- [47].…”
Section: Introductionmentioning
confidence: 99%